TINJAUAN YURIDIS TENTANG PENERAPAN ANCAMAN PIDANA MATI DALAM TINDAK PIDANA KORUPSI - Denny Latumaerissa (SASI, 2014)
Corruption has become a complex phenomenom in Indonesia which frequently involves the government officials, legislative and judicative. Members, bankers, conglomerates, and also corporation that misuse the state’s finance. As a result, Indonesia must suffer from a huge  loss which directly affects the people’s economy. This criminal act, somehow, must be teckled seriously as it has become a national issue. In addressing that problem, the writer specifically focuses on three crusial sections which composed. Of the regulation of death penalty based on law, the development of thoughts regarding the existence of death penalty, and also factors that influence the implementation of death penalty on corruption. As a conclusion, the writer points out that overcoming the act of corrupt which refers to an extraordinary crime has been regulated in law of Indonesian Number 31 years 1999 juncto law number 20 year 2001 as an. Effort to solve the corruption. The threat of death penalty which becomes the hardest penalty is settled as a sort of main criminal based om article 10 substantive of law. Moreover, the discussion of death penalty in law number 31 year 1999 juncto law number 20 year 2001 about counter-corruption, is also stated in article 2 verse (2), however its implementation depends on the requirement indicated in the law. Last but not least is the substantial factor that impedes the implementation of the death penalty which points out the lack of seriousness of legislative members in formulating the sanction of dead penalty as stated in law number 31 year 1999 juncto law number 20 year 2001, which indeed prevent the law enforcement to be implemented successfully in Indonesia